A tradição em movimento: possibilidades de ressignificação da dança popular na escola formal (Revista NUPEART, 2021)
The article deals with the theoretical discussion that guided a research on possibilities of reframing popular dance at school. The work took place in art classes at a school in the interior of Paraíba, with high school students who are immersed in a local culture of producing xaxado. The movement patterns and techniques of this dance were the starting point for an artistic work, where the approaches took place in order to promote the reading and the transformation of the movement through a process of contextualization of the world experienced by the student. The article brings, among others, the contributions of Nestor Garcia Canclini, Carlos Rodrigues Brandão and Isabel Marques to a reflection on how popular dances are connected with modernity, as the discourse of tradition is still a strong inhibitor of work with dance at school and how it is possible to reframe dance in a creative process that uses popular culture as material.
Keywords: Popular dance teaching; Dance Education; School